CFD modelling of multiphase flow in static mixer / Viknesvaran Silverrajan - Viknesvaran, Silverrajan (2020)
Modelling of Multiphase flow through a Kenics static mixer were presented in this paper. Multiphase mixing is a challenging process in industries such as pharmaceutical, food and petroleum since two-different phases can be immiscible towards each other. Stirred tank mixing is the most common method used in industries. However, this type of method costs a lot in terms of energy and manpower specially when mixing immiscible liquids. Hence, The Kenics Static Mixer could be a good solution for multiphase mixing when its correctly configured and studied. Two phases used in this paper were aqueous solution: refined CMC as continuous phase and oil: silicon oil 50 as dispersed phase. The first part of this paper is validation of the simulation. For this purpose, a CFD modelling journal selected and compared. After the validation, the same model was used to study the effect of static mixer blade twist angle and length on the pressure drop and mixing efficiency. The modelling involved a static mixer with 10 blades inserted in clockwise and anti-clockwise manner. For the validation purpose, the pressure drop across a blade is compared with the journal and the mixing efficiency is validated by observing the local volume fraction distribution for the dispersed phase. Then, the effect of twisting angle on static mixer performance studied by twisting the blade with angle of 1800, 1500, 1200 and 900. And then, the 1800 blade is used to study the effect of blade length with the variation of 30mm, 33.75mm, 37.5mm, 41.25mm and 45mm. The ansys R3 student version were used to simulate. The validation of pressure drops showed good agreement with the literature for Reynolds number of 100 and 200. The study on mixing performance showed good agreement with the literature eventhough the pattern were not exactly same. This could be due to the limitation of 512K mesh cells in ansys student version and the different meshing technique were applied. The 900 degree blade outperform the standard 1800 degree blade in terms of pressure drop and mixing performance. The pressure drop could be reduced from 15kPa to 9.8kPa. The quantitative analysis of mixing performance showed that 900 degree blade had better uniformity index compared to 1800 degree blade. The length of the blade does not show a significant effect on the pressure drop nor mixing efficiency.